Relationship between unmet needs for assistance and healthy aging among disabled older adults in China - Cao, Yang; Feng, Yuxin; Luo, Yaling (Frontiers in Public Health, 2022)
Background: Although there is a growing consensus around the world that long-term care services and supports are important to help aged population with disabilities achieve healthy ageing, a misallocation of care resources and inefficiency in care delivery still exist in China. The absence of and inadequate long-term care services and supports among older adults with disabilities results in a range of adverse health-related consequences. However, the negative influence of unmet needs for assistance on healthy ageing, based on functional perspectives including physiological, psychological, and societal domains, has been underestimated. This study aims to measure healthy ageing based on a person-centered approach and examine the relationship between unmet needs for assistance and healthy ageing among older adults with disabilities in China. Methods: Based on the data from the Chinese Longitudinal Healthy Longevity Survey 2018, we used the latent profile analysis with three indicators to uncover distinctive types of older adults experiencing distinct levels of healthy ageing, and applied the ordered logit regression to analyze the correlation between unmet needs for assistance and different levels of healthy ageing. To further address the endogeneity bias, the robust test was conducted by the two-stage least-squares instrumental variables estimator and conditional mixed process instrumental variables estimator. Results: Three ordered latent classes were identified: low level of healthy ageing (42.83%), middle level of healthy ageing (47.27%), and high level of healthy ageing (9.90%). Disabled older adults with unmet need had lower probability of achieving higher level of healthy ageing (OR=0.57, SE=0.04, CI=0.48-0.66, p<0.001). Conclusions: This study highlights the need to increase awareness among gerontological practitioners with respect to long-term care services and supports for disabled older adults as a potential for enhancing their healthy ageing, and that unmet needs could be a basis for risk assessment and a means for determining the efficacy of long-term care interventions on maintaining health.